Exploring the experiences of department heads in promoting positive work ethics among educators - Peter Babajide Oloba; Melisha Govender (Multidisciplinary Journal of School Education)
Research objectives (aims) and problem(s): Poor work ethics among educators in disadvantaged schools remain a persistent challenge, undermining teacher performance, learner outcomes, and institutional effectiveness. Despite their pivotal role in enforcing professional standards, little is known about how department heads experience and navigate their responsibilities in promoting ethical workplace behaviour. This study explores the experiences of department heads in promoting positive work ethics among educators in disadvantaged schools. The study aims to examine how department heads lead efforts to promote positive work ethics and to understand the challenges they face in doing so.